Ontological Foundations in Islamic Sociology - Hossein Ajdarizadeh (Islām va ̒ulūm-i ijtimā̒ī)
The author of the present paper tries to view the ontological foundations of sociology from the Quranic perspective. Using the verses of the holy Quran, he considers God, man, earth, and the relationship between man and other men as four main components of a human society. Centralizing two elements, i.e. man and his relationship, he makes an analysis of either of them and then deals with two other elements and their impact on these two element. Such an approach has turned the current man-oriented sociology into a God-oriented one within which man is just a trustee. According to this view of the Quran, man is a two-dimensional being: celestial and terrestrial, i.e. he has an infinite desire both for virtues and vices. This will also occur in human society which is the product of individuals' thoughts, views, moralities and tendencies. In this approach, three elements of power, cognition, and opposite tendencies pave the way for the most distinctive feature of man, i.e. man's free will. According to the Holy Quran, too much involvement of man and human society in animal tendencies and external affairs (nature and earth), on the one hand, and man's oblivion of his divine self and disobedience to God, on the other hand, will result in man's individual and collective alienation. The most important factor for removal of this stat is obedience to God and knowledge of real self. The author finally concludes that in order to have a full view of human society we should always pay due attention to two main elements of society, that is, man and community. The sort of relationship between these two elements and God and nature has an important impact on man's individual and social behavior.